Odpowiedzi

Najlepsza Odpowiedź!
2010-04-06T18:42:28+02:00
Prosze o rozwiaznie chociaz po a i f) z kazdego . dzięki

1
a
x+2/x-2=0
x+2=0
x=-2
f
x²+5/3x²-6x=0
x²+5=0
sprzeczny
1a
x+1/x+2=x+2/x-3
(x+1)(x-3)=(x+2)²
x²-3x+x-3=x²+4x+4
-6x=7
x=-7/6
f
2x+3/4x-5=4x+5/8x-7
(2x+3)(8x-7)=(4x-5)(4x+5)
16x²-14x+24x-21=16x²-25
10x=-4
x=-0,4
3
a
x/2=8/x
x²=16
x=4 lub x=-4
f
3/x²-4=1
3=x²-4
x²=7
x=√7 lub x=-√7
4a
6/x=x-1 /*x
6=x²-x
x²-x-6=0
Δ=1+24=25
√Δ=5
x=-2 lub x=3
f
x-5/x+1-1=x+1
x-5-(x+1)=(x+1)²
x-5-x-1=x²+2x+1
x²+2x+7=0
Δ=4-28<0
nie ma rozwiązania